Variations of Soil Cyanobacteria Communities Accompanied by Different Habitat Types in Abandoned Ion-Absorbed Rare Earth Tailings - Liu, Yan; Zhang, Meng; Feng, Bing; Chen, Ming; Zhou, Xiuxiu (Journal of Environmental Science and Engineering Technology, 2022)
Soil fertility declined, companied with the poor capacity of water holding, after rare earth mining for a long time, mine tailings remediation produced in conventional rare earth elements REEs exploitation are currently urgent issues. Cyanobacteria are prokaryotic oxygenic phototrophs, played a vital role in the biogeochemical cycling of carbon (C) and nitrogen (N), reducing soil loss, are the pioneer organisms of biological soil crusts BSCs. However, studies on cyanobacteria inoculation in abandoned ionic rare earth mines were still insufficient. The abundance and composition of microorganisms in the topsoil of abandoned ionic rare earth mines were analyzed using high-throughput sequencing of the 16S rRNA V4 gene in this study. Fifteen samples were selected in and around rare earth mine tailings based on five different habitat types to assess the difference of main bacteria component and the dominant cyanobacteria caused by environmental factors. A total of 713,057 effective 16S rRNA genes were classified into 30 bacteria phyla, and 7 cyanobacterial genera were determined in phyla of Cyanobacteria. Proteobacteria, Chloroflexi, Acidobacteria, Actinobacteria, Planctomycetes, and Cyanobacteria were dominant groups in all samples (>5% of total effective sequences). Only Microcoleus, Leptolyngbya, Microcystis, Stigonema, Chroococcidiopsis, Phormidium, and Lyngbya were determined in rare earth mine tailings. Leptolyngbya was wildly distributed in rare earth tailings except for natural woodland, while Microcoleus was found in all of the studying areas in this study. Mining activities could cause the amount of unknown cyanobacteria specie pnr_Chloroplast abnormal. Additionally, results showed that cyanobacteria community composition was not correlated with soil organic matter SOM, but cyanobacteria richness and diversity were limited by the high content of ammonia nitrogen, and Leptolyngbya and Microcoleus could apply to abandoned ion-absorbed rare earth mining tailings repairment.